MANAJEMEN KONFLIK DALAM PENYELESAIAN PERMASALAHAN HUBUNGAN INDUSTRIAL (Studi Dalam Bidang Hubungan Industrial Dinas Tenaga Kerja Kabupaten Pasuruan) - Dhulhijjahyani, Firdausi; Sjamsuddin, Sjamsiar; Nuh, Mohammad (FIA UB, 2020)
In the interaction of industrial relations, there will be differences in thinking between the company management and workers that can cause industrial relation disputes. Such conflicts are commonly known as industrial relations disputes. In this regard, it is expected that the government be able to create a good environment in the industrial sector in order to resolve conflicts or disputes that occur in industrial relations or minimize possible conflicts by linking to relevant agencies in the employment sector. Efforts and supports are necessary to resolve industrial relations disputes/conflicts for the continuity of the company's business, the life of workers and their families, and the stability of the national economy. This study is aimed at describing and analyzing 1) conflict management in the process of dispute resolution in Industrial Relations in Pasuruan Regency and 2) the role of the Manpower Agency in resolving industrial relations in Pasuruan Regency in the perspective of Conflict Management.